SMART BLOOD BANK MANAGEMENT SYSTEM USING IOT - Pooja Huggi; Ankita Birajdar; Ashwini Biradar; Divya Patil; Megha Toran (International Educational Journal of Science and Engineering, 2026)
Blood is a vital part of human life and has a crucialrole in supporting modern medical treatments. Every day, thousands of people require blood transfusions due to accidents, surgeries, childbirth complications, anemia, cancer treatments and other medical emergencies. Blood banks often struggle with shortages of specific blood groups, expired or contaminated blood units, inefficient inventory tracking and lack of coordination between multiple blood banks and hospitals. Traditional blood bank management is carried out manually, leading to human errors, delays in data updates and lack of real-time information. To address these issues, a Smart Blood Bank Management System using IoT technology is proposed that integrates smart sensors, cloud connectivity and automated systems to monitor blood storage conditions, inventory levels and transportation in real time. The system uses IoT-enabled hardware including Arduino UNO, DHT11 temperature sensor, weight sensors, GSM and Wi-Fi modules, interfaced with a cloud-based backend and a responsive web frontend. Real-time data collection, automated SMS alerts, and cloud dashboards enable centralized monitoring and timely supply of safe blood. The system demonstrates significant improvements in efficiency, accuracy and emergency responsiveness over existing manual systems.